2000
DOI: 10.1074/jbc.275.16.12243
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Presence of Peroxisome Proliferator-activated Receptor (PPAR) α and γ and Retinoid Z Receptor in Cartilage

Abstract: Peroxisome proliferator-activated receptor (PPAR) ␣, PPAR␥, and retinoid acid receptor-related orphan receptor (ROR) ␣ are members of the nuclear receptor superfamily of ligand-activated transcription factors. Although they play a key role in adipocyte differentiation, lipid metabolism, or glucose homeostasis regulation, recent studies suggested that they might be involved in the inflammation control and especially in the modulation of the cytokine production. This strongly suggests that these transcriptional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
93
2
8

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(113 citation statements)
references
References 42 publications
9
93
2
8
Order By: Relevance
“…Our findings are at variance with those of Bordji et al, who did not observe any effect of 500 M CloF on 35 S sulfate incorporation and nitrite production in rat chondrocytes in culture (20). This discrepancy could be explained either by interspecies differences in PPAR␣ ligand recognition as already described by others (21), or by the different experimental procedures used.…”
Section: Discussioncontrasting
confidence: 57%
“…Our findings are at variance with those of Bordji et al, who did not observe any effect of 500 M CloF on 35 S sulfate incorporation and nitrite production in rat chondrocytes in culture (20). This discrepancy could be explained either by interspecies differences in PPAR␣ ligand recognition as already described by others (21), or by the different experimental procedures used.…”
Section: Discussioncontrasting
confidence: 57%
“…Within joints, several types of cells could support the antiinflammatory potency of PPAR␥ agonists, since this PPAR isotype is expressed constitutively in synoviocytes (24), macrophages (19), and chondrocytes (36). In addition, each cell type has pathophysiologic relevance to joint inflammation by their production of mediators of inflammation or matrix-degrading enzymes and can therefore be considered a pharmacologic target for PPAR␥ agonists (37).…”
Section: Discussionmentioning
confidence: 99%
“…PPARG2 activation prevents the expression of several inflammatory genes responsible for the pathogenesis of OA, including interleukin-1β, inducible nitric acid synthase, cyclo-oxygenase-2 and microsomal prostaglandin-E2 synthase-1 4–7. There is also some evidence to suggest that PPARG2 activation may be chondroprotective by negatively regulating the expression of matrix metalloproteinase-1 and matrix metalloproteinase-13 and by preventing proteoglycan degradation 4589. It has also been shown that treatment with a PPARG2 activator, pioglitazone, shows beneficial effects in an experimental model of OA 10.…”
mentioning
confidence: 99%